Dopamine-Mediated Circadian and Light/Dark-Adaptive Modulation of Chemical and Electrical Synapses in the Outer Retina - Goel, Manvi; Mangel, Stuart C. (Frontiers in Cellular Neuroscience, 2021)
The vertebrate retina, like most other brain regions, undergoes relatively slow alterations in neural signaling in response to gradual changes in physiological conditions (e.g., activity changes to rest), or in response to gradual changes in environmental conditions (e.g., day changes into night). As occurs elsewhere in the brain, the modulatory processes that mediate slow adaptation in the retina are driven by extrinsic signals (e.g., changes in ambient light level) and/or by intrinsic signals such as those of the circadian (24-h) clock in the retina. This review describes and discusses the extrinsic and intrinsic modulatory processes that enable neural circuits in the retina to optimize their visual performance throughout day and night as the ambient light level changes by ~10 billion-fold. In the first synaptic layer of the retina, cone photoreceptor cells form gap junctions with rods and signal cone-bipolar and horizontal cells. Distinct extrinsic and intrinsic modulatory processes in this synaptic layer are mediated by long-range feedback of the neuromodulator dopamine. Dopamine is released by dopaminergic cells, interneurons whose cell bodies are located in the second synaptic layer of the retina. Distinct actions of dopamine modulate chemical and electrical synapses in day and night. The retinal circadian clock increases dopamine release in the day compared to night, activating high-affinity dopamine D4 receptors on cones. This clock effect controls electrical synapses between rods and cones so that rod-cone electrical coupling is minimal in the day and robust at night. The increase in rod-cone coupling at night improves the signal-to-noise ratio and the reliability of very dim multi-photon light responses, thereby enhancing detection of large dim objects on moonless nights. Conversely, maintained (30 min) bright illumination in the day compared to maintained darkness releases sufficient dopamine to activate low-affinity dopamine D1 receptors on cone-bipolar cell dendrites. This non-circadian light/dark adaptive process regulates the function of GABAA receptors on ON-cone-bipolar cell dendrites so that the receptive field surround of the cells is strong following maintained bright illumination but minimal following maintained darkness. The increase in surround strength in the day following maintained bright illumination enhances the detection of edges and fine spatial details.